Unpredicted spontaneous extrusion of a renal calculus in an adult male with spina bifida and paraplegia: report of a misdiagnosis. Measures to be taken to reduce urological errors in spinal cord injury patients - Singh Gurpreet; Soni Bhakul M; Hughes Peter L; Vaidyanathan Subramanian; Mansour Paul; Sett Pradipkumar (BMC Urology, 2001)
Abstract Background A delay in diagnosis or a misdiagnosis may occur in patients with spinal cord injury (SCI) or spinal bifida as typical symptoms of a clinical condition may be absent because of their neurological impairment. Case presentation A 29-year old male, who was born with spina bifida and hydrocephalus, became unwell and developed a swelling and large red mark in his left loin eighteen months ago. Pyonephrosis or perinephric abscess was suspected. X-ray of the abdomen showed left-sided staghorn calculus. Since ultrasound scan showed no features of pyonephrosis or perinephric abscess, he was prescribed a prolonged course of antibiotics for infection presumed to arise from the site of metal implant in spine. He developed a discharging sinus, following which the loin swelling and red mark subsided. About three months ago, he again developed a red mark and minimal swelling in the left loin. Ultrasound scan detected no abnormality in the renal or perinephric region. Therefore, the red mark and swelling were attributed to pressure from the backrest of his chair. Five weeks later, the swelling in the left loin burst open and a large stone was extruded spontaneously. An X-ray of the abdomen showed that he had extruded the central portion of the staghorn calculus from left kidney. With hindsight, the extruded renal calculus could be seen lying in the subcutaneous tissue of left loin lateral to the 10th rib in the X-ray of abdomen, which was taken when he presented with red mark and minimal swelling. Conclusion This case illustrates how mistakes in diagnosis could occur in spinal cord injury patients, and highlights the need for corrective measures to reduce urological errors in these patients. Voluntary reporting of urological errors is recommended to facilitate learning from our mistakes. In the patients who have marked spinal curvature, ultrasonography of kidneys and perinephric region may not be entirely reliable. As clinical symptoms and signs may be non-specific in SCI patients, they require prompt, detailed and occasionally, repeated investigations. A joint team approach by health professionals belonging to various medical disciplines, which is strengthened by frequent, informal and honest discussions of a patient's clinical condition, is likely to reduce urological errors in SCI patients.